Prelude to Genocide Arusha, Rwanda, and the Failure of Diplomacy - Rawson, David (Ohio University Press, 2018)
As the initial US observer, David Rawson participated in the 1993 Rwandan peace talks at Arusha, Tanzania. Later, he served as US ambassador to Rwanda during the last months of the doomed effort to make them hold. Despite the intervention of concerned states in establishing a peace process and the presence of an international mission, UNAMIR, the promise of the Arusha Peace Accords could not be realized. Instead, the downing of Rwandan president Habyarimana's plane in April 1994 rekindled the civil war and opened the door to genocide. In Prelude to Genocide, Rawson draws on declassified documents and his own experiences to seek out what went wrong. How did the course of political negotiations in Arusha and party wrangling in Kigali, Rwanda, bring to naught a concentrated international effort to establish peace? And what lessons are there for other international humanitarian interventions? The result is a commanding blend of diplomatic history and analysis that is a milestone read on the Rwandan crisis and on what happens when conflict resolution and diplomacy fall short. Published in partnership with the ADST-DACOR Diplomats and Diplomacy Series.